(untitled) (Research, Society and Development, 2023)
The red-fleshed pitaya, also called “red pitaya” (Hylocereus polyrhizus), stands out among many species due to the abundance of components found in its skin and pulp. The objective of this work is to carry out physical, bromatological, phytochemical and toxicological analyzes in search of obtaining data and scientific proof of the bioactive compounds existing in the fruit of the species Hylocereus polyrhizus. The studies carried out are of an experimental and mixed nature, quantitative and qualitative, carried out on samples obtained in the city of Belém, in the State of Pará. Pitaya is a citrus fruit that contains bioactive and essential compounds that could be confirmed in analyzes such as alkaloids, flavonoids , saponins and anthraquinones, in addition to considerable amounts of ascorbic acid (vitamin C). As for the soluble solids content, the average observed was 3.43 (21°C) Brix and pH of 4.21 with the positive presence of reducing sugars. The physical character of the fruit was promising when compared to other literature, with average diameters reasonably superior to species from other regions at 83.47mm, something that benefits trade and consumption. However, excessive intake of a food by the population can lead to toxicity in the body, and it is feasible for toxicological research such as the determination of methemoglobin to demonstrate the reliability of exotic species such as pitaya, as they contain safe concentrations of this molecule, with a maximum average of 1.85% against 2% of the acceptable parameter. In view of this, it is important to seek and prove new sources of beneficial chemical compounds to be used, both for possible pharmaceutical purposes and nutritional use, through fresh consumption of the fruit.